2012
DOI: 10.5144/0256-4947.2012.200
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C virus infection and human immunodeficiency virus in a cohort of Egyptian hemophiliac children

Abstract: BACKGROUND AND OBJECTIVEThe risk of blood-borne infections, especially hepatitis C virus (HCV) and human immunodeficiency virus (HIV) infection still remains in developing countries among children receiving blood products as hemophiliacs, but the risk is not known in Egypt. The objective of this study was to detect the prevalence of HCV and HIV infection among hemophiliac children to know the magnitude of the problem and determine potential risk factors.PATIENTS AND METHODSThis was a cross-sectional study cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…The significant association between previous blood transfusion& occurrence of HCV infection, is in agreement with that reported by Abdelwahab et al (2012) (22) who stated that HCV prevalence rates are higher among previously transfused patients. This might be before the era of blood testing for viruses in blood banks or the blood donor carrying HCV virus but in the incubation period which not appear in the laboratory testing (false negative HCV-Ab by ELISA).…”
Section: Discussionsupporting
confidence: 82%
“…The significant association between previous blood transfusion& occurrence of HCV infection, is in agreement with that reported by Abdelwahab et al (2012) (22) who stated that HCV prevalence rates are higher among previously transfused patients. This might be before the era of blood testing for viruses in blood banks or the blood donor carrying HCV virus but in the incubation period which not appear in the laboratory testing (false negative HCV-Ab by ELISA).…”
Section: Discussionsupporting
confidence: 82%
“…This result is in agreement with that reported by Arafa et al (2005) (19) who concluded that Community and informal health provider related exposures were associated with increased HCV infection. The significant association between previous blood transfusion& occurrence of HCV infection, is in agreement with that reported by Abdelwahab et al (2012) (22) who stated that HCV prevalence rates are higher among previously transfused patients. This might be before the era of blood testing for viruses in blood banks or the blood donor carrying HCV virus but in the incubation period which not appear in the laboratory testing (false negative HCV-Ab by ELISA).…”
Section: Hepatitis C Virus (Hcv) Infection Is a Major Public Health Csupporting
confidence: 82%
“…High prevalence levels were reported among subpopulations such as hemodialysis patients (range = 27.1–98%; median = 67.5%), multi-transfused patients (range = 17.6–54.9%; median = 38.2%), and thalassemia patients (range = 8.9–82%; median = 50.0%). A single study among hemophilic children reported anti-HCV prevalence at 40.0% 63 . The only study among PWID assessed anti-HCV prevalence at 63% 64 .…”
Section: Resultsmentioning
confidence: 99%
“…HCV viremic rate was reported among the general population (range = 26.9–100%; median = 65.3%; Supplementary Table S2 ) and its subpopulations including children (range = 33.3–75.9%; median = 41.0%), pregnant women (range = 26.9–79.0%; median = 55.1%), and other general populations (range = 29.7–100%; median = 69.5%). Among populations at high risk (Supplementary Table S3 ), HCV viremic rate was reported among thalassemia patients (range = 55–100%; median = 74.3%), and was measured at 100% 143 among multi-transfused children, and at 47.5% 63 among hemophilic children.…”
Section: Resultsmentioning
confidence: 99%